2015
DOI: 10.1016/j.neuro.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The cannabinoid receptor antagonist AM251 increases paraoxon and chlorpyrifos oxon toxicity in rats

Abstract: Organophosphorus anticholinesterases (OPs) elicit acute toxicity by inhibiting acetylcholinesterase (AChE), leading to acetylcholine accumulation and overstimulation of cholinergic receptors. Endocannabinoids (eCBs, e.g., arachidonoyl ethanolamide [AEA] and 2-arachidonoyl glycerol [2-AG]) are neuromodulators that regulate neurotransmission by reducing neurotransmitter release. The eCBs are degraded by the enzymes fatty acid amide hydrolase (FAAH, primarily involved in hydrolysis of AEA) and monoacylglycerol li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…It is, in part, comprised of (a) the CB1 receptor; (b) two principal endogenous ligands (2‐arachidonoylglycerol and anandamide [AEA]); (c) the serine hydrolases monoacylglycerol lipase; (d) and endocannabinoid metabolizing enzymes (fatty acid amide hydrolase [FAAH] and monoacylglycerol lipase) (Di Marzo et al, ), as well as other signaling pathways involved in neurodevelopment (Berghuis, ; Dalton & Howlett, ). CPF has been shown to disrupt this system in adult (Liu & Pope, ; Nomura et al, ; Nomura & Casida, ; Quistad, Klintenberg, Caboni, Liang, & Casida, ; Quistad, Nomura, Sparks, Segall, & Casida, ; Quistad, Sparks, & Casida, ) and preweaning rats (Buntyn et al, ; Carr, Adams, Kepler, Ward, & Ross, ; Carr et al, ; Carr, Graves, Mangum, Nail, & Ross, ). Furthermore, the endocannabinoid system is partly involved in anxiety responses (Carr et al, ; Ruehle, Rey, Remmers, & Lutz, ).…”
Section: Neurodevelopmental and Neurobehavioral Effects Of Cpf In Rodmentioning
confidence: 99%
“…It is, in part, comprised of (a) the CB1 receptor; (b) two principal endogenous ligands (2‐arachidonoylglycerol and anandamide [AEA]); (c) the serine hydrolases monoacylglycerol lipase; (d) and endocannabinoid metabolizing enzymes (fatty acid amide hydrolase [FAAH] and monoacylglycerol lipase) (Di Marzo et al, ), as well as other signaling pathways involved in neurodevelopment (Berghuis, ; Dalton & Howlett, ). CPF has been shown to disrupt this system in adult (Liu & Pope, ; Nomura et al, ; Nomura & Casida, ; Quistad, Klintenberg, Caboni, Liang, & Casida, ; Quistad, Nomura, Sparks, Segall, & Casida, ; Quistad, Sparks, & Casida, ) and preweaning rats (Buntyn et al, ; Carr, Adams, Kepler, Ward, & Ross, ; Carr et al, ; Carr, Graves, Mangum, Nail, & Ross, ). Furthermore, the endocannabinoid system is partly involved in anxiety responses (Carr et al, ; Ruehle, Rey, Remmers, & Lutz, ).…”
Section: Neurodevelopmental and Neurobehavioral Effects Of Cpf In Rodmentioning
confidence: 99%
“…Liver homogenates were clarified by centrifugation at 1000 g at 4 8C for 10 min using an Avanti J-25I centrifuge (Beckman Coulter), and the supernatant was used for assays. Acetylcholinesterase, butyrylcholinesterase, and monoacylglycerol lipase were measured using the photometric method of Ellman et al (1961) as modified by Ulloa and Deutsch (2010) and Liu and Pope (2015). A cocktail (175 mL) of substrate (final concentrations: acetylthiocholine, 1 mM; butyrylthiocholine, 1 mM; 2arachidonoyl thioglycerol, 0.1 mM) along with 5,5 0 -dithiobis (2-nitrobenzoic acid) (0.1 mM final) in 10 mM Tris buffer containing 1 mM EDTA (pH 7.2; Tris-E) was added to tissue homogenates (25 mL) in a final reaction volume of 200 mL.…”
Section: Biochemical Assaysmentioning
confidence: 99%
“…Indeed, we previously reported that acute toxicity of both paraoxon (the active metabolite of parathion) and diisopropylfluorophosphate, is reduced by CB1 receptor agonists (Nallapaneni et al ., 2006, 2008; Wright et al ., 2010). More recently, the CB1 receptor antagonist AM251 was shown to increase the acute toxicity of paraoxon and chlorpyrifos oxon (the active metabolite of chlorpyrifos; Liu and Pope, 2015). …”
Section: Introductionmentioning
confidence: 99%